The relationship between situational determinants of use and drinking motives. (2nd January 2018) - Blevins, Claire E.; Abrantes, Ana M.; Stephens, Robert S.
Abstract: Objective: Recent research has focused on motives as proximal factors of alcohol use that relate to problematic outcomes. High-risk situations for use are also salient predictors of use and negative consequences, and there is some evidence to suggest that situations of use align with motives for alcohol use. The goal of the current study was to examine whether situational use variables can potentially be a proxy for motives for use by evaluating the relationships between motives, rates of alcohol use, and situational use variables (situations of use, locations of use, use companions). Methods: We utilized data from a randomized controlled treatment trial of a brief personalized feedback intervention and subsequent online assessments that focused on motives for alcohol use among 303 college students (77.9% female, mean age = 19.8 years). Results: Results substantiated several theoretical relationships between Social motives and drinking in positive affect situations with others, Coping motives and drinking alone in negative affect-driven situations, Enhancement and use in positive affective situations, and Conformity and drinking in situations that are not indicative of pleasant emotions. However, we failed to find significant relationships with overall rates of use except for among Enhancement-oriented drinkers. Conclusion: Results provide insight into the relationships between motives and situations of use. Findings broadly support the use of situational measures as an indicator of motives and suggest future avenues of research and intervention.